Law and economics approaches to corporate governance - Cankar, Nina; Deakin, Simon; Simoneti, Marko (LeXonomica, 2021)
This paper provides a critical assessment of existing theoretical approaches to corporate governance within law and economics. Conventional economic approaches to law, new institutionalism and behavioural science, as well as the transplant literature, are discussed and their limits indicated. We suggest that by incorporating novel concepts, such as receptiveness, familiarity, adaptation, and internal process of development, the evolutionary dynamics of law and economics signifies a tendency towards corporate governance analysis that involgves the study of institutional change and deals with questions that cannot be easily quantified. Such perspective invites a further look into the nature and evolution of legal norms and opens a way for a review of corporate governance arrangements from the perspective of unconventional socio-legal theories. Pravni in ekonomski vidiki upravljanja družb. Prispevek kritično ovrednoti obstoječe teoretične pristope ekonomske analize prava na področju upravljanja družb, s poudarkom na klasični ekonomski analizi prava, teoriji t. i. novega institucionalizma in literaturi s področja transplantacije pravnih norm ter z namenom opredeliti in nakazati njihove meje. Moderni pristopi, ki so v analizo pravnih pravil vpeljali nekatere nove koncepte, kot so dovzetnost, prilagodljivost in notranji proces razvoja, nakazujejo trend v smeri obravnavanja področja upravljanja družb s pomočjo elementov, ki se jih težje meri in kvantificira. Takšen pristop zahteva podrobno obravnavo narave in razvoja pravnih norm ter s tem odpira pot analizi korporacijskega upravljanja z vidika manj znanih teorij prava in sociologije.